HECLINET — Health Care Literature Information Network - Schaad, R.; Swertz, P. (Methods of Information in Medicine, 1977)
In the field of hospital care there lias been cooperation between various European hospital institutes in the last few years. Since 1970, a working party for information and documentation has been in operation, which was institutionalized as a Study Committee of the International Hospital Federation in 1973.A survey of this Study Committee showed a large degree of parallel and multiple work being done in the European documentation centers for hospital care. With a view to avoiding this duplication of work, a sensible division of labour has been initiated since 1968 by the Institute for Hospital Building of the Technical University of Berlin and the German Hospital Institute — an institute affiliated to the University of Düsseldorf. Thereby the national hospital literature is being indexed in the individual countries, but centrally collected, suitable for EDP. A magnetic tape service and an on-line access to a data bank in Düsseldorf are offered to the hospital institutes concerned.Within the framework of the network system, the original literature cited is made available to the partners on microfiche.For official institutionalization of the documentation network, an organizational concept has been developed, termed HECLINET (.Health Care. Literature information JVeiwork), which is at present being discussed with all the institutions concerned.
Keywords: Data Network; Literature Documentation; Hospital Care